Development of a multi-representation-based calculus e-module to improve students' mathematical literacy skills - Bq. Malikah Hr; Sukandi Sukandi; Alpiana Hidayatulloh; Baiq Susdiana Fibrianti (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2026)
The study aims to develop a multi-representation-based calculus e-module and to examine its effectiveness in improving students’ mathematical literacy skills. The research method employed was research and development (R&D) using the DDD-E model. The effectiveness of the e-module was tested through a quasi-experimental design with a pretest-posttest control group design and analysed using ANCOVA based on students’ pretest and posttest scores. The subjects were 62 first-semester students of the Civil Engineering Department at Mandalika University of Education, consisting of 32 students in the experimental class and 30 students in the control class. The results indicated that the developed e-module was validated by subject-matter, learning, and design experts and was effective in improving students’ mathematical literacy skills. The ANCOVA results showed a significance value of p < 0.001, which is less than 0.05, indicating a significant difference between the class that received treatment using the multi-representation-based e-module and the control class. The average posttest score of the experimental class (70.19) was higher than that of the control class (55.77), indicating that the use of a multi-representation-based calculus e-module had a positive impact on students’ mathematical literacy skills. In addition, the effect size value was 0.868, which was categorised as a large effect size. This result indicates that the developed e-module had a strong effect on improving students’ mathematical literacy skills. These findings suggest that the multi-representation-based calculus e-module is effective in improving students’ mathematical literacy skills and is suitable for implementation in calculus learning, particularly in the civil engineering program.